Pressure-induced phase transition of SnH4: a new layered structure. Issue 13 (26th January 2016) - Zhang, Huadi; Jin, Xilian; Lv, Yunzhou; Zhuang, Quan; Li, Ying; Bao, Kuo; Li, Da; Liu, Bingbing; Cui, Tian
Abstract : Using a structure searching technique, a new layered metallic phase for SnH4 with a C 2/ m symmetry was obtained at high pressure. Abstract : The lattice structure, electronic properties, and superconductivity of SnH4 under high pressure were determined by first-principle calculations. A new layered structure C 2/ m with charge transfer from the Sn to H atoms was predicted to be the most stable high-pressure form. In the layered structure, each Sn atom combines with four H atoms and two H2 units, forming six Sn–H bonds of very similar lengths. The rich and multiple Fermi surface distribution in the Brillouin zone shows metallic features with the conductivity deriving from the electrons around the hydrogen atoms. The estimated high T c of ca. 64–74 K at 500 GPa is attributed to the strong electron–phonon coupling from the vibration phonon modes of the H atoms.